The Alfa Program: a case study of a concrete experience towards academic integration - Solanas, Facundo (FCL-UNESP Laboratório Editorial, 2007)
The Alfa Program fits in the public procedures of mobility and interchange in the European Union with the purpose of consolidating the process of regional integration. Contradictory as it may seem, this program is one of the few instruments that are able to increment the interchange of teachers, students and researchers with the Mercosul, the Southern Common Market. Having in mind the objectives and the structure of the Alfa Program, this paper analyses qualitatively its method and theory from the point of view of the agents involved. In order to accomplish this task, a case study of one of its intrauniversity nets is presented: Alfa Euro – Cone Sul (Southern Common Market).